The redistributive impact of consumption taxation in the EU: Lessons from the post-financial crisis decade - Sofia Maier; Mattia Ricci (European Commission, Joint Research Centre (JRC), 2022)
During the 2010-2019 decade, consumption taxes have risen in the vast majority of the EU Member States as a result of austerity measures, tax shifts as well as taxing transport and housing-related energy consumption. The redistributive impact of these policy changes remains mostly unexplored. In this paper, we provide new empirical evidence on the redistributive effect of changes in VAT and excises over this period, along with other developments in the broader tax-benefit system including tax shift reforms. Our results indicate that the consumption tax systems in the EU have become more unequalizing in most countries as a result of an increase in the tax burden and of its regressivity. While the taxation of transport is the component that has increased the most, the highest inequality impact was driven by the taxation of housing-related energy consumption. Only in a few countries these policy changes were accompanied by an increase in social transfers sufficient to compensate the poorest households.
Keywords: C81; D31; H20; H22; 330; Consumption taxation; Tax shift; Austerity; Inequality; Microsimulation